2022
DOI: 10.3171/2021.3.jns204329
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of visual area with tremor improvement after MRgFUS thalamotomy in Parkinson’s disease

Abstract: OBJECTIVE MRI-guided focused ultrasound (MRgFUS) thalamotomy is a novel and minimally invasive alternative for medication-refractory tremor in Parkinson’s disease (PD). However, the impact of MRgFUS thalamotomy on spontaneous neuronal activity in PD remains unclear. The purpose of the current study was to evaluate the effects of MRgFUS thalamotomy on local fluctuations in neuronal activity as measured by the fractional amplitude of low-frequency fluctuations (fALFF) in patients with PD. METHODS Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…These FC changes were correlated with clinical improvement of tremor. In line with Xiong et al ( 42 ) we observed the involvement of the second-order, functionally highly-specialized, visual area in the pathogenesis of tremor in PD. Also, such contribution was already evidenced in ET ( 37 , 40 , 41 , 89 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These FC changes were correlated with clinical improvement of tremor. In line with Xiong et al ( 42 ) we observed the involvement of the second-order, functionally highly-specialized, visual area in the pathogenesis of tremor in PD. Also, such contribution was already evidenced in ET ( 37 , 40 , 41 , 89 ).…”
Section: Discussionsupporting
confidence: 92%
“…There is only one report investigating the impact of MRgFUS Vim thalamotomy on the neuronal activity in a whole-brain level ( 42 ). In particular, the authors measured fractional amplitude of low-frequency fluctuations (fALFF) on nine medication-refractory of patients with TD-PD, finding significant changes in visual areas at 12 months after the treatment compared to baseline ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trajectory of some of these changes not only corresponds to increasing motor deficits, in line with dopaminergic neuron loss ( 2 ), but also non-axial symptoms ( 5 ) that highlights their heterogeneous nature. Interestingly, a recent study found that therapy-resistant patients with PD who underwent thalamotomy exhibit changes of low-frequency fluctuations in the primary visual cortex that correspond to improving hand tremor symptoms ( 6 ). In addition, patients with PD who report visual hallucinations were shown to have abnormal activation patterns in the occipital and temporal extrastriate cortices ( 7 ), where structural changes also manifest ( 8 ).…”
Section: Introductionmentioning
confidence: 99%